Therapeutic potential of the gut commensal bacterium Parabacteroides goldsteinii in human health and disease treatment - Li, Ziyun; Zhang, Li; Wan, Zhenxia; Liu, Huijuan; Zhang, Ting; Li, Yan (Frontiers in Microbiology, 2025)
The gut microbiota, as a critical guardian of human health, maintains physiological homeostasis, modulating immunity, and facilitates nutrient metabolism. Parabacteroides goldsteinii, a probiotic gut commensal, has garnered increasing scientific attention. This review systematically examines its biological characteristics, then analyzes mechanisms promoting health (immunomodulation, metabolic regulation, and intestinal barrier reinforcement), and finally evaluates disease associations (metabolic disorders, neurological diseases, inflammatory conditions, and malignancies). Current evidence shows that therapeutic efficacy against obesity, non-alcoholic fatty liver disease, inflammatory bowel disease, autism spectrum disorder, and colorectal cancer via short-chain fatty acids secretion, bile acid transformation, and host immunity modulation. Dietary factors (e.g., inulin), pharmacological agents (e.g., metformin, aspirin), and lifestyle interventions (e.g., exercise synbiotics) dynamically regulate its abundance, underscoring therapeutic potential. Despite translational challenges–like optimizing cultivation, dose-response characterization, and genetic tool development–emerging applications (engineered probiotics, fecal microbiota transplantation, and synthetic biology) highlight broad prospects. Future research should prioritize context-dependent mechanisms across diseases and refined translation strategies for microbiome-based precision medicine.